HIATUSES AND EROSION SURFACES - Afanas'yev S.L. (My University, 1989)
Detailed stratigraphic schemes of the Upper Cretaceous sediments in the Caucasus allowed us to identify the presence of hiatuses and intraformational erosion surfaces based on the omission of one or another stratigraphic unit or a reduction in the number of natural cyclites within a stratigraphic unit. Hiatuses and intraformational erosion surfaces were found at the boundary between the Lower and Upper Campanian and at the base of the Cenomanian, Upper Turonian, and Danian. The durations of the hiatuses were estimated on the basis of the number of natural cyclites missing from a section when checked against the Novorossiysk reference section. In all, there were 42 hiatuses encompassing a total of 11,797 natural cyclites. The average numerical density of eroded cyclites among all cyclites from the 5th to 12th orders, with the exception of cyclites of the 9th and 10th orders, is a constant.
Keywords: Turonian; Cenomanian; Campanian; Danian; Cretaceous; Кайнозой::Палеоген::Палеоцен::Датский; Mesozoic::Cretaceous::Upper::Campanian; Mesozoic::Cretaceous; Cenozoic::Paleogene::Paleocene::Danian; Mesozoic::Cretaceous::Upper::Turonian; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая::Верхний::Кампанский; Мезозой::Меловая; Мезозой::Меловая::Верхний::Туронский; Мезозой::Меловая::Верхний::Сеноманский